2010
DOI: 10.1108/17422041011086823
|View full text |Cite
|
Sign up to set email alerts
|

Informal networks as “global microstructures”: the case of German expatriates in Russia

Abstract: PurposeMultinational companies are considered “driving forces” of globalization and “prime movers” of global sociation. Yet the problems, conflicts, and contradictions in the implementation of global strategies at the micro level – as well as the real possibility that such implementation will fail – are virtually ignored in macro‐sociological studies. Hence, the purpose of this paper is to address this neglect by focusing on a micro level examination of the contribution of expatriates in their interactive role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Finally, the impacts of international business activities have also been studied by looking at actors that actively promote IB, such as expatriates, migrating professionals and the globally mobile middle class. These studies focus on problems of identity construction and the hardships of working abroad (Boussebaa and Morgan, 2008;Wagner and Vormbusch, 2010;Kosmala and Xian, 2011;Blazejewski, 2012;McCann, 2013;Moore, 2016;Santamaria Alvarez and Sliwa, 2016;Mielly et al, 2017;Fitzpatrick, 2017 as well as the papers found in the special issue entitled "Critical perspectives on the globally mobile professional and managerial class" edited by McKenna et al (2015; issue 2).…”
Section: Effects Of International Business Activitiesmentioning
confidence: 99%
“…Finally, the impacts of international business activities have also been studied by looking at actors that actively promote IB, such as expatriates, migrating professionals and the globally mobile middle class. These studies focus on problems of identity construction and the hardships of working abroad (Boussebaa and Morgan, 2008;Wagner and Vormbusch, 2010;Kosmala and Xian, 2011;Blazejewski, 2012;McCann, 2013;Moore, 2016;Santamaria Alvarez and Sliwa, 2016;Mielly et al, 2017;Fitzpatrick, 2017 as well as the papers found in the special issue entitled "Critical perspectives on the globally mobile professional and managerial class" edited by McKenna et al (2015; issue 2).…”
Section: Effects Of International Business Activitiesmentioning
confidence: 99%